Plant potential for foodstuff in Tangale Nature Reserve - SITI SUNARTI; RUGAYAH RUGAYAH; TUTIE DJARWANINGSIH (Society for Indonesian Biodiversity, 2007)
Tangale is one of nature reserve in Gorontalo province, with covers about 113 ha areas but information on plant biodiversity especially, which has potency as source of foodstuff is still limited. For that reason a plant exploration and inventory in this area has been made in 2002. Thirty-three species of edible plant have been recorded, and they consist of fruits (19 species), vegetables (12 species), cereal (1 species) and tuber (1 species). According to local people those 19 species have been used for daily necessity.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Foodstuff, Biodiversity, Tangale Nature Reserve.